Potential applications of horseshoe crab in biomedical research - Ibrahim, Najian; Kannan, Thirumulu Ponnuraj; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah (Advanced Medical and Dental Institute (AMDI, USM), 2019)
Horseshoe crab is one of the oldest existing living fossils comprising four main species today. Of these, Limulus Polyphemus is found in North America and the other three species, Tachypleus tridentatus, Tachypleus gigas and Carcinoscorpius rotundicauda are found in Southeast Asia. Horseshoe crabs play important roles in the regulation of the coastal ecology communities whereby the eggs serve as the main diet of shorebird species during the migrating season. Horseshoe crab is also seen as a versatile organism, useful in the biomedicine field particularly, as its blue blood has been widely integrated to be used for endotoxin tester in vaccines, drugs and injectables. Researchers have explored a material called perivitelline fluid (PVF) from the egg of a fertilized horseshoe crab which is rich in important proteins and amino acids that are crucial for embryogenesis. Previous studies have shown that PVF has the ability to enhance cell growth and differentiation as well as in promoting generation of certain organs. Testing of PVF on many types of cells has shown positive results and hence, it is suggested that PVF could be used as a supplement to support cell growth in future. Highlighting the horseshoe crab as a living fossil, this review brings out the relevance of the blue blood and PVF of the horseshoe crab as sources benefitting molecular research.